2016
DOI: 10.1016/j.rhm.2016.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Gender norms as health harms: reclaiming a life course perspective on sexual and reproductive health and rights

Abstract: Despite their demographic significance and the lifetime impact of gender disparities on their health and rights, women considered older than reproductive age are excluded from most investments in global public health. While development policies linking human rights with access to sexual and reproductive healthcare have yielded progress towards improving the status of women and girls, older women have not benefited from these initiatives. Yet as women grow older, they experience a range of health conditions roo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 17 publications
0
10
0
2
Order By: Relevance
“…Los sistemas crean y recrean desigualdades teniendo en cuenta los aspectos sociales, políticos, culturales, personales e históricos de cada una de ellas. En el sistema biomédico se acentúan estos aspectos, a través de la medicalización, falta de autonomía en los procesos de saludenfermedad y otras formas de violencia institucionalizada, las que se presentan como forma de control social hacia quienes no se enmarcan en el prototipo androcéntrico y hegemónico de quién ejerce el poder (Gomes & Couto, 2014;Linardelli, 2015;Tasa-Vinyals et al 2015;Pitter, 2016;Cassiano et al 2016;Crockett & Cooper, 2016;Zacher, 2015).…”
Section: Género Diferencias Y Accesosunclassified
See 1 more Smart Citation
“…Los sistemas crean y recrean desigualdades teniendo en cuenta los aspectos sociales, políticos, culturales, personales e históricos de cada una de ellas. En el sistema biomédico se acentúan estos aspectos, a través de la medicalización, falta de autonomía en los procesos de saludenfermedad y otras formas de violencia institucionalizada, las que se presentan como forma de control social hacia quienes no se enmarcan en el prototipo androcéntrico y hegemónico de quién ejerce el poder (Gomes & Couto, 2014;Linardelli, 2015;Tasa-Vinyals et al 2015;Pitter, 2016;Cassiano et al 2016;Crockett & Cooper, 2016;Zacher, 2015).…”
Section: Género Diferencias Y Accesosunclassified
“…En tanto, en otros ámbitos de la salud y la vida en sociedad "el cuerpo de las mujeres es un estereotipo «construido» socialmente, centrado en la maternidad" (Urrea, 2014, p. 194); gran parte de los estudios e investigaciones realizados en los últimos años en cuanto a mujeres y salud refieren principalmente a los procesos relativos a la atención del parto y están de acuerdo en la existencia de un encasillamiento y estereotipo femenino vinculado a la maternidad y a los cuidados de la progenie (Urrea, 2014;Panisello & Pastor, 2015;Tajer et al, 2015;Crockett & Cooper, 2016;Triuzzi, 2017), transformándole "en un lugar de subordinación para las mujeres" (Triuzzi, 2017, p. 101), así se invisibiliza a aquellas otras mujeres que se encuentran fuera de la edad reproductiva dado que en la salud femenina se enfatiza la maternidad (Crockett & Cooper, 2016).…”
Section: Estereotiposunclassified
“… 21 Menopause and the end of fertility leaves women aged 50+ neglected in a health care agenda framed through a lens of reproductive function. 22 , 23 Thus, gender-responsive SH research which interrogates the social landscape of ageing 23 has been identified as a priority area for scholarship. 23 , 24 …”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, concerns about older people’s SRH and rights (a) continue to be a taboo topic and (b) of little interest to researchers and professionals in the healthcare field. Despite the widespread agreement, the life course approach to addressing SRH and rights has received minimal attention [ 14 17 ]. Moreover, as India moves closer to Universal Health Coverage, it is important to assess if policy initiatives to broaden women’s health beyond maternal health and family planning have increased women’s service utilization.…”
Section: Introductionmentioning
confidence: 99%